Perbandingan Hasil Revised Distribution Method dan Metode Stepping Stone dengan Penentuan Nilai Awal Menggunakan Metode North West Corner dalam Meminimumkan Biaya Pendistruibusian Barang - Zulaiha Eka Saputri; Yuki Novia Nasution; Wasono Wasono (Program Studi Statistika FMIPA Universitas Mulawarman, 2019)
Globalization and free trade era make the distribution of goods as if not limited by region. In the process of distribution of goods, cost calculation becomes a very important factor, to minimize the cost of distribution, it is necessary to apply a transportation modeling. Revised Distribution Method (RDI) is a method of transportation that does not use initial solutions in its completion. The RDI method is different with the Stepping Stone Method that uses the initial solution to determine the optimal solution. The purpose of this research is to minimize the cost of distribution of LPG gas 3 Kg using RDI and Stepping Stone method and then compare the two methods to see optimal results. The result shows that RDI method has 10 iterations with minimum cost of Rp 26.719.520,- thus saving 41% with cost difference of Rp 18.280.480,- from previous transportation cost of Rp 45.000.000,- while Stepping Stone method has 4 iterations with result a minimum charge of Rp 24.000.000,- thus saving 47% with a difference of Rp 20.968.000,- from the previous fee of Rp 45.000.000,-. So it can be concluded that the stepping stone method is a more appropriate method to minimize the amount of transportation costs at PT. Tri Pribumi Sejati.